Satellite remote sensing-based in-season prediction of optimal nitrogen rates for corn under diverse on-farm conditions - Junjun Lu; Yuxin Miao; Katsutoshi Mizuta; Renzo Negrini; Peter Anthony; Lorena N. Lacerda; Kirk Stueve; Matt Wiebers (Computers and Electronics in Agriculture, 2026)

Electrospinning air filtration membrane modified by interfacial optimized hollow nanozyme for efficient antibacterial PM removal - Xueying Qi; Junjun Lu; Xinjiao Wang; Xinxin Xu (Journal of Environmental Chemical Engineering, 2026)

Developing an improved remote sensing and calibration strip-based nitrogen management strategy for corn - Junjun Lu; Yuxin Miao; Xiong Du; Fabián G. Fernández (European Journal of Agronomy, 2026)

Leucobacter faecis sp. nov., a Novel Actinomycete Isolated from Bat Feces of Rousettus and Hipposideros spp. - Yuyuan Huang; Jing Yang; Qinglian Qin; Zedan Yang; Xiaoting Wei; Ziwei Lin; Wenbo Luo; Wudi Wei; Zongxiang Yuan; Li Ye; Junjun Jiang; Shan Lu; et al. (Current Microbiology, 2026)

Regulation spin state in CuCo2O4 nanozyme by heterojunction construction with polyoxometalate for detoxiﬁcation of mustard gas simulants - Junjun Lu; Xinxin Xu; Jin Chen; Qiang Wang (Journal of Hazardous Materials, 2026)

Warm-season non-refractory PM2.5 composition in urban Tianjin and Beijing: Two megacities of the North China Plain - Qingqing Wang; Lu Lei; Yanpei Li; Wei Hu; Libin Wu; Junjun Deng; Jin Feng; Chun Chen; Borong Cheng; Jiang Zhu; Pingqing Fu; Yele Sun; et al. (Journal of Environmental Sciences, 2026)

Optimization of bridge pier plastic hinge length using machine learning and pushover analysis - Xinle Yao; Hui Jiang; Jingyu Wang; Xinzhi Dang; Qiang Lian; Xingji Lu; Junjun Guo (Engineering Structures, 2026)

Interfacial charge redistribution in CuCo2O4/PMo12 p-n heterojunction nanozymes optimizes d-band center for robust antibiofouling solar seawater desalination - Junjun Lu; Jiajia Wang; Hongbo Cao; Xinxin Xu; Qiang Wang (Chemical Engineering Journal, 2026)

Urban Surface Deformation Monitoring Enhanced by E-SBAS: Multi-Source 3D Time-Series Integration - Xiaoyu Zhang; Shitai Wang; Min Yin; Zhengyang Xu; Zengyang Lu; Junjun Huang; Songchao Yu (Advances in Space Research, 2026)

Performance evaluation and mechanism analysis of different ice particle distribution shape parameter schemes in BCC-AGCM - Pengcheng Lin; Chunsong Lu; Yiming Liu; Xin He; Junjun Li; Tongwen Wu; Yixiong Lu (Atmospheric Research, 2026)

Improving Asian summer monsoon cloud and precipitation simulations through an ice crystal spectral relative dispersion parameterization - Xin He; Chunsong Lu; Jian Cao; Wentao Zhang; Hengqi Wang; Lei Zhu; Junjun Li; Xiaoqi Xu; Xiangjun Shi; Yuan Wang (Science China Earth Sciences, 2026)

Mining and characterization of novel prolyl endopeptidases from human gut microbes for degrading the immunogenic gluten 33-mer peptide - Xiaojing Zhou; Pan Huang; Chuan Zhang; Chengcheng Zhang; Gang Wang; Shumao Cui; Wenwei Lu; Bo Yang; Junjun Wu; Xiaomei Lyu; Fengwei Tian; Jianxin Zhao; et al. (Food Bioscience, 2026)

Plantaricin-producing Lactiplantibacillus plantarum NDF28B2 as an adjunct culture enhances fermented Milk texture and suppresses Listeria monocytogenes - Nan Xiao; Yang Liu; Chengcheng Zhang; Chuan Zhang; Pan Huang; Gang Wang; Shumao Cui; Wenwei Lu; Bo Yang; Junjun Wu; Xiaomei Lyu; Fengwei Tian; et al. (Food Research International, 2026)

Coupled evaluation of the pros and cons of fluorochemical industry for sustainable development - Xinyue Shao; Pei Wang; Zhenjun Zhang; Junjun Hu; Yonglong Lu (Journal of Cleaner Production, 2026)

Enhanced osteogenic differentiation of rBMSCs under low-frequency dynamic stimulation of piezoelectric membranes - Jing Liu; Donglin Li; Xiaoqing Liu; Jiahao Zeng; Yuxuan Lu; Weiqiang Fan; Shuncheng Zhang; Yuxuan Jia; Linxuan Zheng; Xin Chen; Hongzhang Deng; Yongmei Wang; et al. (Chemical Engineering Journal, 2026)

Distinct phylogenetic patterns and assembly processes of abundant and rare taxa in traditional grain vinegar fermentation ecosystem - Mingye Peng; Bo Li; Yunli Zhu; Lu Guo; Lei Deng; Zhicong Shen; Zhiwen Jia; Yang Chen; Junjun Gao; Mengzhou Zhou (International Journal of Food Microbiology, 2026)

Reconstructing historical cloud ice water fraction using machine learning and multi-source satellite data from 1983 to 2009 - Dezhi Xiao; Chunsong Lu; Sinan Gao; Jiashan Zhu; Yang Li; Ru Zhou; Junjun Li; Jing Yang; Naifu Shao (Atmospheric Research, 2026)

Experimental study and seismic performance analysis of novel damage-free self-centering devices with variable stiffness, high-energy dissipation and low prestress - Xin Li; Hui Jiang; Liangjiang Chen; Junjun Guo; Yongzheng Zhou; Wenliang Lu; Cong Zeng (Engineering Structures, 2025)

The interfacial optimization and p-n heterojunction construction in nanozyme for improved laccase-mimic and antibiofouling activities - Xueying Qi; Junjun Lu; Yueming Li; Xinxin Xu (Journal of Environmental Chemical Engineering, 2025)

The combined effects of convective entrainment and orographic drag on precipitation over the Tibetan Plateau - Junjun Li; Chunsong Lu; Jinghua Chen; Xu Zhou; Kun Yang; Xiaoqi Xu; Xianghua Wu; Lei Zhu; Xin He; Shiying Wu; Pengcheng Lin (Science China Earth Sciences, 2025)

Evolutionary repeatability of chromatin accessibility in the hippocampus between echolocating bats and soft-furred tree mice - Luye Shi; Yuanshuo Ma; Qinyang Hua; Junjun Hao; Qin Zhang; Yaxin Ye; Lu Yang; Qi Liu; Peng Chen; Zhen Liu; Peng Shi (Science China Life Sciences, 2025)

The construction of p-n heterojunction in nanozyme for improved peroxidase-like activity and “point-of-use” water disinfection - Junjun Lu; Kequan Yao; Xinxin Xu; Jinzhao Ou; Qiang Wang (Chemical Engineering Journal, 2025)

Self-assembling biocompatible core-shell nanocapsules with versatile surface functionalities for precise pesticide delivery - Chunlin Yang; Zaiyu Lu; Chunhui Zhou; Xiang Yao; Yawei Tang; Xiuxia Li; Junjun Wang; Lihong Zhang (Chemical Engineering Journal, 2025)

Impact of stochastic collisions on cloud droplet number concentration and relative dispersion during Meiyu frontal system - Jingxi Sun; Chunsong Lu; Yan Yin; Sinan Gao; Junjun Li; Yiwei Zhang (Atmospheric Research, 2025)

Insights from Computational Fluid Dynamics and In Vitro Studies for Stent Protrusion in Iliac Vein: How Far Shall We Go? - Zhenmin Fan; Jian Lu; Hao Cheng; Xia Ye; Xiaoyan Deng; Pengfei Zhao; Junjun Liu; Mingyuan Liu (Cardiovascular Engineering and Technology, 2025)

Bromodomain and extraterminal domain (BET) promote autophagy in buffalo sertoli cells - Yuan Yang; Junjun Zhang; Yue Zhang; Qinqiang Sun; Ruixin Liu; Chunrong Xu; Peng Xu; Yangqing Lu; Qiang Fu (Theriogenology, 2025)

The cost of rural environmental degradation in China: An integrated evaluation framework and city-level case study - Wentao Lu; Huihui Zhao; Ye Qiang; Junjun Chen; Yang Guan; Guosheng Wang; Changbo Qin (Environmental Impact Assessment Review, 2025)

Amylopectin from maize-derived carbonized polymer dots as a novel high-efficiency antioxidant for periodontitis treatment - Junjun Liu; Naibo Feng; Xinyu Jiang; Xirui Xin; Yubo Hou; Zhende Jiang; Laijin Lu; Weixian Yu; Bai Yang (Chemical Engineering Journal, 2024)

Developing a new active canopy sensor- and machine learning-based in-season rice nitrogen status diagnosis and recommendation strategy - Junjun Lu; Erfu Dai; Yuxin Miao; Krzysztof Kusnierek (Field Crops Research, 2024)

Blood–Brain Barrier Permeability is Affected by Changes in Tight Junction Protein Expression at High-Altitude Hypoxic Conditions—this may have Implications for Brain Drug Transport - Guiqin Liu; Qian Wang; Lu Tian; Mengyue Wang; Delong Duo; Yabin Duan; Yue Lin; Junjun Han; Qiangqiang Jia; Junbo Zhu; Xiangyang Li (The AAPS Journal, 2024)

Temperature sensitivity of aerobic and anaerobic organic carbon mineralization varies with climate and soil depth in riparian zones - Mingzhu Lu; Gang He; Lei Fan; Guihua Liu; Junjun Wu; Wenzhi Liu; Lin Ma (Soil Biology and Biochemistry, 2024)

Metal vacancies and self-reconstruction of high entropy metal borates to boost the oxygen evolution reaction - Mengyuan Zhang; Kongliang Luo; Yaning Fan; Xiaoyan Lu; Jian Ye; Nana Lu; Jiali Dong; Qiang Niu; Junjun Zhang; Pengfei Zhang; Sheng Dai (Chemical Engineering Journal, 2024)

Application of microbially induced calcium carbonate precipitation (MICP) process in concrete self-healing and environmental restoration to facilitate carbon neutrality: a critical review - Junjun Chang; Dongyang Yang; Cheng Lu; Zhitao Shu; Shengjiong Deng; Liwei Tan; Shaoqing Wen; Ke Huang; Pengchang Duan (Environmental Science and Pollution Research, 2024)

The influence of complex terrain on cloud and precipitation on the foot and slope of the southeastern Tibetan Plateau - Junjun Li; Chunsong Lu; Jinghua Chen; Xu Zhou; Kun Yang; Jian Li; Xiaoqing Wu; Xiaoqi Xu; Shiying Wu; Rui Hu; Xin He; Zhuangzhuang Zhou; et al. (Climate Dynamics, 2024)

Acidity-activated degradable Mn-engineered silicon nanohybrids coordinated with iprodione for high-efficiency management of Sclerotinia sclerotiorum and nutrient enhancement to crops - Fengrui Zhang; Min Fang; Peijie Hu; Xiang Yao; Chunlin Yang; Zaiyu Lu; Junjun Wang; Lihong Zhang (Chemical Engineering Journal, 2024)

The Probability Density Function Related to Shallow Cumulus Entrainment Rate and Its Influencing Factors in a Large-Eddy Simulation - Lei Zhu; Chunsong Lu; Xiaoqi Xu; Xin He; Junjun Li; Shi Luo; Yuan Wang; Fan Wang (Advances in Atmospheric Sciences, 2024)

Knowledge, Attitude, and Practice of Breast Cancer Patients Toward Lymphedema Complications: Cross-Sectional Study - Yan Qin; Junjun Lu; Shanze Li; Jie Huang; Wenjing Teng; Yue Wu; Wanqing Chen; Lizhen Wang; Weikang Zhu (Journal of Cancer Education, 2023)

Observational study of relationships between entrainment rate, homogeneity of mixing, and cloud droplet relative dispersion - Chunsong Lu; Lei Zhu; Yangang Liu; Fan Mei; Jerome D. Fast; Mikhail S. Pekour; Shi Luo; Xiaoqi Xu; Xin He; Junjun Li; Sinan Gao (Atmospheric Research, 2023)

Identification of LBH and SPP1 involved in hepatic stellate cell activation during liver fibrogenesis - Weiming Dai; Yuecheng Guo; Zhenyang Shen; Junjun Wang; Lungen Lu; Hui Dong; Xiaobo Cai (Human Cell, 2023)

Impacts of regional uplift of the Tibetan Plateau on local summer precipitation and downstream moisture budget: A simulation study - Kai Yang; Jinghua Chen; Chunsong Lu; Junjun Li; Tianyu Liu; Liping Deng; Yanwei Li (International Journal of Climatology, 2022)
Using the Weather Research and Forecasting (WRF) model, a series of sensitivity experiments were conducted to study the individual and overall effects of the various topographic uplifts of the Tibetan Plateau (TP) on regional climate variability. The presence of the southern slope of the TP facilitates the maintenance and development of the South Asia High (SAH), which produces a positive cyclic response between local precipitation and SAH, so that the northern branch of the South Asian summer monsoon (SASM) maintains the water vapor supply. At the same time, the southern slope of the TP has a positive effect on the mid‐latitude tropospheric anomalous cyclone and anticyclone systems which promotes the downstream advancement of the East Asian summer monsoon (EASM) and is favourable for the transfer of water vapor and convective clouds downstream. The role of the TP platform is mainly due to the lifting of moisture generated by its local heating, which favours the formation of local convective clouds and precipitation while causing nonadiabatic warming of the troposphere. Water vapor transported from the TP could affect precipitation in central‐eastern China (CEC). However, the supply of water vapor in Southern East China (SEC) mainly comes from the southeast coast of China. The Tibetan Plateau sensitive areas (TPSA) have impacts on the water vapor transport path. Removing the TPSA favours an increase in precipitation and convective clouds in SEC. The removal of topographic disturbances favours the convergence and dispersion of water vapor at mid‐latitudes. The mid‐latitude dynamical anomaly may form a standoff with the low‐latitude dynamical system. This leads to inefficient precipitation and convective generation processes, a weakened monsoon advance over land, and a southward shift in the rainfall belt.

Effect and Mechanism of Cotrimoxazole Against Talaromyces marneffei in vitro - Jie Chen; Rongfeng Chen; Wudi Wei; Fengxiang Qin; Xiu Chen; Jinhao He; Hong Zhang; Gang Wang; Minjuan Shi; Tongxue Qin; Yinlu Liao; Yuting Wu; et al. (Mycopathologia, 2022)

Relationships between Cloud Droplet Spectral Relative Dispersion and Entrainment Rate and Their Impacting Factors - Shi Luo; Chunsong Lu; Yangang Liu; Yaohui Li; Wenhua Gao; Yujun Qiu; Xiaoqi Xu; Junjun Li; Lei Zhu; Yuan Wang; Junjie Wu; Xinlin Yang (Advances in Atmospheric Sciences, 2022)

Association between plasminogen activator inhibitor-1 gene polymorphisms and susceptibility to Parkinson’s disease in Chinese patients - Qi Xu; Qilun Lai; Junjun Wang; Liying Zhuang; Lin Cheng; Yejia Mo; Lu Liu; Zexian Zhao; Ying Zhang; Shiting Weng; Song Qiao (Acta Neurologica Belgica, 2022)

Accuracy assessment and climatology of MODIS aerosol optical properties over North Africa - Abou Bakr Merdji; Xiaofeng Xu; Chunsong Lu; Birhanu Asmerom Habtemicheal; Junjun Li (Environmental Science and Pollution Research, 2022)

Correction to: Can “new infrastructure” reverse the “growth with pollution” profit growth pattern? An empirical analysis based on listed companies in China - Lu Qiao; Lin Li; Junjun Fei (Environmental Science and Pollution Research, 2022)

Can “new infrastructure” reverse the “growth with pollution” profit growth pattern? An empirical analysis based on listed companies in China - Lu Qiao; Lin Li; Junjun Fei (Environmental Science and Pollution Research, 2022)

Genetic control and phenotypic characterization of panicle architecture and grain yield-related traits in foxtail millet (Setaria italica) - Hui Zhi; Qiang He; Sha Tang; Junjun Yang; Wei Zhang; Huifang Liu; Yanchao Jia; Guanqing Jia; Aiying Zhang; Yuhui Li; Erhu Guo; Ming Gao; et al. (Theoretical and Applied Genetics, 2021)

QTL mapping for foxtail millet plant height in multi-environment using an ultra-high density bin map - Qiang He; Hui Zhi; Sha Tang; Lu Xing; Suying Wang; Haigang Wang; Aiying Zhang; Yuhui Li; Ming Gao; Haijin Zhang; Guoqiu Chen; Shutao Dai; et al. (Theoretical and Applied Genetics, 2021)

Transcriptome and metabolome analysis of Pichia stipitis to three representative lignocellulosic inhibitors - Yuanyuan Zhu; Lu Wu; Junjun Zhu; Yong Xu; Shiyuan Yu (Archives of Microbiology, 2019)

Devonian integrative stratigraphy and timescale of China - Wenkun Qie; Xueping Ma; Honghe Xu; Li Qiao; Kun Liang; Wen Guo; Junjun Song; Bo Chen; Jianfeng Lu (Science China Earth Sciences, 2019)

Stability assessment of a new antithrombotic small peptide, Arg-Gly-Asp-Trp-Arg (RGDWR), and its derivative - Lijun Yang; Litao Zhang; Lihong Yan; Haifeng Zheng; Peifen Lu; Junjun Chen; Jie Dai; Haibiao Sun; Yong Xu; Tao Yang (Biotechnology Letters, 2017)

Greenhouse wastewater treatment by baffled subsurface-flow constructed wetlands supplemented with flower straws as carbon source in different modes - Junjun Chang; Luyao Ma; Jinquan Chen; Yifeng Lu; Xiaoyun Wang (Environmental Science and Pollution Research, 2017)

Soil organic matter quantity and quality shape microbial community compositions of subtropical broadleaved forests - Junjun Ding; Yuguang Zhang; Mengmeng Wang; Xin Sun; Jing Cong; Ye Deng; Hui Lu; Tong Yuan; Joy D. Van Nostrand; Diqiang Li; Jizhong Zhou; Yunfeng Yang (Molecular Ecology, 2015)
As two major forest types in the subtropics, broadleaved evergreen and broadleaved deciduous forests have long interested ecologists. However, little is known about their belowground ecosystems despite their ecological importance in driving biogeochemical cycling. Here, we used Illumina MiSeq sequencing targeting 16S rRNA gene and a microarray named GeoChip targeting functional genes to analyse microbial communities in broadleaved evergreen and deciduous forest soils of Shennongjia Mountain of Central China, a region known as ‘The Oriental Botanic Garden’ for its extraordinarily rich biodiversity. We observed higher plant diversity and relatively richer nutrients in the broadleaved evergreen forest than the deciduous forest. In odds to our expectation that plant communities shaped soil microbial communities, we found that soil organic matter quantity and quality, but not plant community parameters, were the best predictors of microbial communities. Actinobacteria , a copiotrophic phylum, was more abundant in the broadleaved evergreen forest, while Verrucomicrobia , an oligotrophic phylum, was more abundant in the broadleaved deciduous forest. The density of the correlation network of microbial OTU s was higher in the broadleaved deciduous forest but its modularity was smaller, reflecting lower resistance to environment changes. In addition, keystone OTU s of the broadleaved deciduous forest were mainly oligotrophic. Microbial functional genes associated with recalcitrant carbon degradation were also more abundant in the broadleaved deciduous forests, resulting in low accumulation of organic matters. Collectively, these findings revealed the important role of soil organic matter in shaping microbial taxonomic and functional traits.

Quinoxaline-2,3-diones: potential d-amino acid oxidase (DAAO) inhibitors - Dongsheng Xie; Yanchao Wang; Jin Xie; Jun Lu; Junjun Cui; Man Zhang; Lei Fu; Yongxiang Wang (Medicinal Chemistry Research, 2014)

A thermo-halo-tolerant and proteinase-resistant endoxylanase from Bacillus sp. HJ14 - Junpei Zhou; Qian Wu; Rui Zhang; Minghe Mo; Xianghua Tang; Junjun Li; Bo Xu; Junmei Ding; Qian Lu; Zunxi Huang (Folia Microbiologica, 2014)

Preliminary genetic linkage maps of Chinese herb Dendrobium nobile and D. moniliforme - SHANGGUO FENG; HONGYAN ZHAO; JIANGJIE LU; JUNJUN LIU; BO SHEN; HUIZHONG WANG (Journal of Genetics, 2013)

Plus- and minus-stranded foot-and-mouth disease virus RNA quantified simultaneously using a novel real-time RT-PCR - Chaojiang Gu; Congyi Zheng; Lili Shi; Qian Zhang; Yong Li; Bin Lu; Yi Xiong; Sanpu Qu; Junjun Shao; Huiyun Chang (Virus Genes, 2007)